1994
DOI: 10.1182/blood.v83.7.1876.bloodjournal8371876
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Wilms' tumor gene (wt1) during myelomonocytic differentiation in HL60 cells

Abstract: The putative Wilms' tumor-suppressor gene (wt1) encodes a zinc finger DNA binding protein that functions as a transcription repressor. The wt1 gene expression corresponds to kidney development, suggesting a role for this gene in nephroblast differentiation. Here we show that wt1 mRNA expression was downregulated during terminal differentiation of promyelocytic HL60 cells. When HL60 cells were induced to differentiate to granulocytes by dimethyl sulfoxide (DMSO) or retinoic acid (RA), a marked downregulation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…This reported that they have found mutations in the WT1 gene in 4 of 36 acute leukemia samples by SSCP analysis. The is consistent with the findings that the WT1 expression was downregulated during the differentiation of HL60 cells by mutations comprise small insertions in exons 1 and 7 and a nonsense mutation in exon 9, predicting the production of a dimethyl sulfoxide or retinoic acid 38 and during induction of erythroid and megakaryocytic differentiation of K562 cells. 39 truncated WT1 protein with absence or disruption of the zinc megakaryocyte-related transcription factor GATA-1.…”
Section: Very Low or Undetectable Levels Of Wt1 Expression Insupporting
confidence: 91%
“…This reported that they have found mutations in the WT1 gene in 4 of 36 acute leukemia samples by SSCP analysis. The is consistent with the findings that the WT1 expression was downregulated during the differentiation of HL60 cells by mutations comprise small insertions in exons 1 and 7 and a nonsense mutation in exon 9, predicting the production of a dimethyl sulfoxide or retinoic acid 38 and during induction of erythroid and megakaryocytic differentiation of K562 cells. 39 truncated WT1 protein with absence or disruption of the zinc megakaryocyte-related transcription factor GATA-1.…”
Section: Very Low or Undetectable Levels Of Wt1 Expression Insupporting
confidence: 91%
“…The human leukaemic cell lines U937, K562 and HL60 were investigated. K562 and HL60 are both known to express high levels of WT1 (Sekiya et al , 1994), whereas U937 lacks detectable WT1 expression (Svedberg et al , 1998). GATA1 expression has been described in K562 (Zhang et al , 1997).…”
Section: Cell Linesmentioning
confidence: 99%
“…These isoforms show differences in DNA binding, affinity and their localization inside the cell (106). During hemopoiesis, WT1 is expressed mainly in CD34 + progenitor cells, and its mRNA levels decrease as the cells differentiate (107–109). The effects of WT1 on gene expression are complex, because it interacts with other transcription regulation factors.…”
Section: Gene Mutationsmentioning
confidence: 99%